Návrh strategie řízení nákupu v nadnárodních společnostech - Macháček, Jiří (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
V této diplomové práci je popsán a analyzován proces strategie řízení nákupu v nadnárodních společnostech. S pomocí teoretických poznatků z literatury a dle analýzy současného stavu strategie řízení nákupu v nadnárodní firmě byla v práci zpracována metodika a strategie řízení nákupu v nadnárodních společnostech.

The process of strategy purchasing management in multinational companies is described and analysed in this master´s thesis. Both methodology and strategy of purchasing management in the multainational companies have been compiled in this work by means of theoretical knowledge from literature and according to the analysis of the current state of purchasing management in a company.
The Draft of Strategy Purchasing Management in Multinational Companies
Keywords: Řízení nákupu; strategie; ABC analýza; nákup dle komodit; Purchasing management; strategy; ABC analysis; purchasing by comodities